Constructing Er-Doped ZnO/CuS/Au Core-Shell Nanowires with Enhanced Photocatalytic and SERS Properties - Chia-Man Chou (MDPI AG, 2021)
In this study, we fabricated Er-doped ZnO/CuS/Au core-shell nanowires using two-step wet chemical methods and an ion-sputtering method on a glass substrate as a bifunctional photocatalytic and surface-enhanced Raman scattering (SERS) substrate. The characteristic properties of as-prepared photocatalysts were confirmed by scanning electron microscopy, X-ray diffraction, transmission electron microscopy, energy-dispersive X-ray spectroscopy, DR/UV-Vis spectroscopy, and photoluminescence spectroscopy. Compared with Er-doped ZnO nanowires and Er-doped ZnO/CuS core-shell nanowires, Er-doped ZnO/CuS/Au core-shell nanowires exhibited remarkably photocatalytic activity to degrade acid orange 7 solutions under blue LED light. These results ascribed to the Er-doped ZnO/CuS/Au core-shell nanowires can enhance the visible-light absorbance and the separation efficiency of photogenerated electron-hole pairs, inducing their higher photocatalytic activity under blue LED light. In addition, Er-doped ZnO/CuS/Au core-shell nanowires exhibit high sensitivity, a low detection limit (10−6 M), uniformity, recyclability, and stability of SERS performance for detected acid orange 7.